Financial Sector Policy Response to COVID-19 in Emerging Markets and Developing Economies - Feyen, Erik; Alonso Gispert, Tatiana; Kliatskova, Tatsiana; Mare, Davide S. (Elsevier, 2021)
This paper introduces a new global database and a policy classification framework that records the financial sector policy response to the COVID-19 pandemic across 155 jurisdictions and over time. It documents that authorities around the world have taken a diverse array of measures to mitigate financial distress in the markets and for borrowers, and to support the provision of critical financial services to the real economy. Using Cox proportional hazards and Poisson regressions, the paper takes initial steps to analyze the determinants of policy makers’ responsiveness and activity in emerging markets and developing economies, respectively. The results indicate that policy makers in richer and more populous countries have been significantly more responsive and have taken more policy measures. Belonging to a monetary union is also significantly associated with a faster and more frequent intervention. Countries with higher private debt levels tend to respond earlier with banking sector and liquidity and funding measures. The spread of COVID-19, macro-financial fundamentals, pressure on foreign exchange markets, political settings, and fiscal and containment policies appear to play a limited role in determining policy response. In a substantially smaller sample, the paper explores the role of banking sector characteristics and finds that emerging markets and developing economies with higher private bank credit to GDP and that have adopted Basel III reforms have taken fewer policy measures.